Fixed-target serial oscillation crystallography at room temperature. (2019) - Wierman, Jennifer L.; Pare-Labrosse, Olivier; Sarracini, Antoine; Besaw, Jessica E.; Cook, Michael J.; Oghbaey, Saeed
No abstract available